Failure to Find a Conditioned Placebo Analgesic Response - Flaten, Magne A.; Bjørkedal, Espen; Lyby, Peter S.; Figenschau, Yngve; Aslaksen, Per M. (Frontiers in Psychology, 2018)
Background: Associative learning has, in several studies, been modulated by the sex of the participant. Consistent with this, a recent review found that conditioned nocebo effects are stronger in females than in males. Purpose: It has been suggested that conditioned placebo responses are stronger in females, and this hypothesis was investigated in the present study. Cortisol and measures of negative emotions were taken to investigate if these processes could mediate any conditioned placebo effects. Methods: Cold pain was applied to the volar forearm. The Conditioned group received inert capsules prior to two presentations of less painful stimulations, to associate intake of the capsules with reduced pain. The Pain control group received the same painful stimulation as the Conditioned group, but no capsules. The Capsule control group received the capsules in the same way as the Conditioned group, but no decrease in the painful stimulation. Subject sex was crossed across groups. It was hypothesized that in the Conditioned group, an expectation of reduced pain should be induced after administration of the capsules, and this should generate placebo analgesia, and mostly so in females. Results: The Conditioned group reported lower pain during conditioning, and rated the capsules as more effective painkillers than the Capsule control group. However, placebo analgesia was not reliably observed in the Conditioned group. Conclusion: The placebo capsules were rated as effective painkillers, but this did not translate into a placebo analgesic effect. This could be due to violation of response expectancies, too few conditioning trials, and differences in pain ratings in the pre-test that could be due to previous experience with painkillers.